Allowing one’s own bodily experience to "count": Elaborating on inter- subjectivity and subjectivity in phenomenological studies - Groven, Karen Synne; Engelsrud, Gunn (Journal of Education and Research, 2013)
Phenomenology, according to Heidegger and Merleau-Ponty, looks at human beings in the world. Drawing on their perspective, one could argue that inter-subjectivity, like a researcher’s subjectivity, should be explicitly acknowledged in phenomenological studies. In the following pages we explore how using this approach can make findings more transparent and trustworthy. This study is based on a review of five articles focused on subjectivity and inter-subjectivity in phenomenological studies. In addition, we draw on the first author’s experiences as a PhD candidate studying to become a “phenomenological” researcher. Our findings reveal that reflecting explicitly on bodily subjectivity during the research process can reveal connections between the context of the interview, how the material is created socially and textually and how the researcher utilized information from her own body in the interpretation of the material. This, in turn, is likely to make the findings more inter-subjective and transparent, and thus more trustworthy and valid. Our findings point to the value of letting one’s own bodily experiences “count” in the process of determining how to explore the phenomena in question. Although the literature offers guidelines, each project and each researcher is unique. In this light, personal reflections are likely to highlight the value of critically engaging – and making explicit – the researcher’s own experiences, both during and after the interview process. DOI: http://dx.doi.org/10.3126/jer.v3i0.7850 Journal of Education and Research March 2013, Vol. 3, No. 1, pp. 24-40